International law theories : an inquiry into different ways of thinking - Bianchi, Andrea, 1963 July 4- (2016)
By providing an overview of the different theoretical approaches to and perspectives on international law, this book takes readers through fourteen of the most important theories of international law, explaining their origins, core components, and the influence they have had.
Different ways of thinking about International law -- Traditional approaches -- Constitutionalism and Global governance -- Marxism -- The New Haven School -- International relations and social science methodologies -- Critical legal studies and the New stream -- The Helsinki School -- Feminism -- Third World approaches -- Legal pluralism -- Social idealism -- Law and economics -- Law and literature.
Includes bibliographical references and index.
Keywords: International law; 86.80 international law: general; 86.03 theory and methodology of law; Law; International law; 2; Theorie; 86.80 international law: general; 86.03 theory and methodology of law; Law